Optimization Injection Molding Parameters of Polypropylene Materials to Minimize Product Not Complete Defects Using the Taguchi Method - Utomo, Apendito Priyo; Bintara, Redyarsa Dharma; Suprayitno (Proceeding International Conference on Religion, Science and Education, 2022)
The plastic manufacturing industry is currently developing in the manufacturing industry field. The plastics manufacturing industry is particularly suitable for mass-producing products of complex sizes. More than 30% of all plastic parts are produced by an injection molding process. The products produced by injection molding machines are not completely perfect. There are some product defects caused by several environmental and machine factors. This product defect is a problem for companies in the manufacturing sector, especially injection molding, as it disrupts production and reduces company profits. Overcoming the product defect results, the researcher chose the Taguchi method since this method was used to analyze and optimize through experimental design, which was completed by conducting a series of methods and experiments to obtain the optimal solution. Therefore, the researcher wants to make and find the parameter settings to minimize a product-not-complete which is detrimental to the company. This research was conducted experimentally by determining the design of the experiment (DoE) using fractional factorial L9 (34) for 3 initial injection cycles, where the test specimen was a bio ball spike product with polypropylene material. The parameters used are injection pressure, injection speed, injection time, and melt temperature with each parameter consisting of 3 levels. The results of the data that have been processed were then calculated by analysis of means (ANOM) to determine the average effect of each parameter at each level and obtain plot effects. Analysis of variance (ANOVA) was also calculated to determine the effect of each parameter on the output which aims to verify the Taguchi method used. Using the results obtained, the researcher knew the effect of each parameter and the optimal combination of parameters to minimize product-not-complete defects. The results of the experimental study indicate that injection pressure and injection time are the dominant factors determining the quality because reducing the pressure that presses the molten plastic material to enter the mold will have an effect on product-not-complete filling.